Analisis Strategi Pemungutan Pajak Restoran dalam Meningkatkan Pendapatan Asli Daerah Dimasa Pandemi Covid-19 (Studi Kasus Bapenda Kota Bekasi Tahun 2021) - Putri Harisah Tastiah; Daryanto Hesti Wibowo (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The more advanced business development of the food and beverage industry should be able to increase local revenue but during the pandemic restaurant tax revenue declined sharply so the government issued policies and tried to improve restaurant tax collection strategies. The purpose of this study was to analyze the strategy of restaurant tax collection in increasing local revenue during the Covid-19 pandemic (Case Study of Bekasi city Bapenda in 2021), the obstacles faced, and efforts to overcome these obstacles. Methods This study uses qualitative research methods are descriptive. In this study the data collection techniques used are observation, interviews, documentation. The data source consists of primary data in the form of observation and documentation, and secondary data in the form of interviews with informants. The results of this study indicate that (1) the restaurant tax collection strategy in increasing local revenue during the pandemic has been going well with the indicators that are run. (2) the obstacles faced by the Bekasi City Regional Revenue Agency in collecting restaurant taxes during the covid-19 pandemic are many restaurants that cannot pay taxes. This is because the restaurant is empty of visitors, the restaurant's operational schedule is limited and the opening and closing hours are limited so that the income or turnover received cannot cover operational costs, a drastic decrease in the number of receipts, conditions for the implementation of business activities are not optimal, making the economy unstable.